Transient migrants at the crossroads of China's global future. Issue 1 (1st March 2019) - Cheuk, Ka-Kin
China has witnessed a remarkable growth in its foreign population over the past two decades. Even though they are still quite few in number at the moment, foreigners in China are being increasingly recognized and studied in the broad field of migration studies. Although they have neither the hope nor the desire to become permanent residents of China, most foreigners nonetheless continue to be construed as 'immigrants' or 'migrants' in both the scholarly and policy-oriented literature. This special issue suggests that applying these terms without problematizing them hinders our understanding of foreigners in the real-world context, in which an increasing number of people have become transient migrants in China and elsewhere. By bringing together articles that depict these foreigners' lives as transient everywhere they go, this special issue aims to develop a new analytical lens through which ongoing global dynamisms in demography, politics and economy – particularly those that matter much to the future of both foreigners and China – can be simultaneously captured.